2022
DOI: 10.3390/ijerph191711139
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, Perceptions and Practices of Influenza Vaccination in the Adult Population: Results of a Cross-Sectional Survey in Spain

Abstract: In Spain, the 2021/22 influenza season overlapped with the sixth wave of the 2019 coronavirus disease pandemic (COVID-19). Influenza is a major public health problem associated with high morbidity and mortality. The objectives of this study were to determine the knowledge, perceptions and practices of influenza vaccination in the Spanish population, coinciding with the COVID-19 pandemic, with special attention paid to people over 65 years of age. A cross-sectional study was carried out by conducting 2211 telep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…This study found that people who had been vaccinated before were 2.981 times more likely to accept influenza vaccination than those who had not been received influenza vaccine before. The result were in line with previous studies in different populations, such older people, 38 , 39 HCWs, 40 , 41 children’s guardians, 42 etc. It was possible that those who had received the influenza vaccine were more likely to trust the safety and effectiveness of the influenza vaccine, making them more willing to receive it again.…”
Section: Discussionsupporting
confidence: 92%
“…This study found that people who had been vaccinated before were 2.981 times more likely to accept influenza vaccination than those who had not been received influenza vaccine before. The result were in line with previous studies in different populations, such older people, 38 , 39 HCWs, 40 , 41 children’s guardians, 42 etc. It was possible that those who had received the influenza vaccine were more likely to trust the safety and effectiveness of the influenza vaccine, making them more willing to receive it again.…”
Section: Discussionsupporting
confidence: 92%
“…This value was higher than the 37.5% in a sample of midwives in France [ 20 ]. As indicated in other surveys, a HCW’s recommendation has been shown to be one of the main factors influencing individual’s perceptions and practices about vaccinations [ 14 , 34 , 35 , 36 ] and the lack of a recommendation is often a reason for not being immunized [ 14 , 37 , 38 , 39 ]. Understanding the barriers is necessary for developing interventions that could increase the vaccination coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In another study it was shown that 79.9% of Healthcare Personnel (HCP) in the United States reported having received an influenza vaccination during the 2021-22 season, which was similar to the account of 75.9% during the 2020-21 season. Moreover, vaccination coverage against influenza was found to be lower among nurses (87.8%), compared to physicians (96.8%) [8].…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, nearly 40% of the unvaccinated said that they had not been vaccinated due to a lack of recommendation or prescription [17]. Considering the role of physicians in vaccinations, these statistics call for actions aimed at addressing vaccine hesitancy and identifying the sources of misinformation regarding vaccines, as well as combating them [18].…”
Section: Resultsmentioning
confidence: 99%